Selective Evolution of Ligands by Exponential Enrichment to Identify RNA Aptamers against Shiga Toxins - Sreerupa Challa; Saul Tzipori; Abhineet Sheoran (Journal of Nucleic Acids)
Infection with Shiga toxin- (Stx-) producing E. coli causes life threatening hemolytic uremic syndrome (HUS), a leading cause of acute renal failure in children. Of the two antigenically distinct toxins, Stx1 and Stx2, Stx2 is more firmly linked with the development of HUS. In the present study, selective evolution of ligands by exponential enrichment (SELEX) was used in an attempt to identify RNA aptamers against Stx1 and Stx2. After 5 rounds of selection, significant enrichment of aptamer pool was obtained against Stx2, but not against Stx1, using a RNA aptamer library containing 56 random nucleotides (N56). Characterization of individual aptamer sequences revealed that six unique RNA aptamers (mA/pC, mB/pA, mC, mD, pB, and pD) recognized Stx2 in a filter binding assay. None of these aptamers bound Stx1. Aptamers mA/pC, mB/pA, mC, and mD, but not pB and pD, partially blocked binding of Alexa 488-labeled Stx2 with HeLa cells in a flow cytometry assay. However, none of the aptamers neutralized Stx2-mediated cytotoxicity and death of HeLa cells.